Karakteristik infeksi Acinetobacter baumannii pada anak yang dirawat di RSUP Sanglah, Bali, Indonesia periode Januari 2017-Desember 2018 - Gusti Ayu Putu Sri Satya Mahayani; I Wayan Gustawan; I Made Gede Dwi Lingga Utama; Ida Bagus Gede Suparyatha; I Made Arimbawa; Ni Made Adi Tarini (Intisari Sains Medis, 2020)
Background: Acinetobacter baumannii is a gram-negative bacterium that can cause nosocomial infections in humans. An increased incidence of A. baumannii infection is accompanied by increased antibiotic resistance and mortality from this bacterial infection. This study aims to determine the characteristic Acinetobacter baumannii infection and the pattern of germ sensitivity of antibiotics in children treated at Sanglah Hospital.Methods: A cross sectional study was conducted in the Pediatric Ward Sanglah Hospital. We performed a retrospective review of medical records from pediatric patients who were proven to have Acinetobacter baumannii infection through microbiological examination from blood culture samples while undergoing treatment in Pediatric Ward Sanglah Hospital from January 2017 to December 2018. Data were analyzed using SPSS version 20 for Windows.Results: A total of 33 pediatric patients were proven to have Acinetobacter baumannii bloodstream infection through microbiological examination. Most of them are males (72.7%) and 57.57% are neonates. Laboratory results obtained mean leukocyte levels 16.2±8.6 x 103/?L, median platelets 113.8 (3.7-464) x 103/?L, and mean procalcitonin 20.0±3.11 ng/ml. The average length of stay before Acinetobacter baumannii infection was 7 days, with the average total length of stay was 29.7 days. Patients who died during treatment were relatively high (45.5%) and 84.8% of them were treated in the intensive care unit, with 30 out of 33 patients infected with A. baumannii multidrug-resistant (MDR). Most patients use medical devices with an average usage time of more than 7 days.Conclusion: Most patients infected by Acinetobacter baumannii are treated in the intensive care unit with a high mortality rate. The A.baumannii bacteria identified were mostly MDR with a history of long-term use of antibiotics and medical devices. Latar Belakang: Acinetobacter baumannii adalah bakteri gram negatif yang dapat menyebabkan infeksi nosokomial pada manusia. Terdapat peningkatan insiden infeksi A. baumannii yang disertai peningkatan kejadian resistensi terhadap antibiotik, serta mortalitas akibat infeksi bakteri ini. Penelitian ini bertujuan untuk mengetahui bagaimana gambaran infeksi Acinetobacter baumannii serta pola sensitifitas kuman terhadap antibiotik pada anak yang dirawat di RSUP Sanglah yang merupakan rumah sakit rujukan di wilayah Indonesia bagian timur.Metode: Studi ini merupakan studi deskriptif dengan pendekatan potong lintang. Studi ini menggunakan data sekunder dari rekam medis pasien anak yang terbukti terinfeksi Acinetobacter baumannii melalui pemeriksaan kultur darah selama dirawat di RSUP Sanglah periode Januari 2017-Desember 2018. Data dianalisis dengan SPSS versi 20 untuk Windows.Hasil: Terdapat 33 pasien dengan kultur darah positif Acinetobacter baumannii. Sebagian besar berjenis kelamin lelaki (72,7%) dan 57,57% merupakan neonatus kurang bulan. Hasil laboratorium didapatkan rerata kadar leukosit 16,2±8,6 x 103/?L, median trombosit 113,8 (3,7- 464) x 103/?L, dan rerata procalcitonin 20,0±3,11 ng/ml. Median lama perawatan sebelum terjadinya infeksi adalah 7 hari dengan rerata lama perawatan 29,7 hari. Pasien yang meninggal selama perawatan cukup tinggi (45,5%) dan 84,8% dari pasien dirawat di ruang intensif dengan 30 dari 33 pasien terinfeksi multidrug resistant (MDR) A. baumannii. Sebagian besar pasien menggunakan alat medis dengan rerata lama pemakaian lebih dari 7 hari.Simpulan: Sebagian besar pasien yang terinfeksi Acinetobacter baumannii dirawat di ruang intensif dengan angka kematian yang cukup tinggi. Kuman A.baumannii yang teridentifikasi sebagian besar bersifat MDR dengan riwayat penggunaan antibiotika serta alat medis dalam jangka waktu lama.